Intestinal spirochaetosis. Issue 820 (February 1994) - Lo, T. C.; Heading, R. C.; Gilmour, H. M.
Abstract : Two cases of intestinal spirochaetosis are described. The first case improved with treatment while the second case improved spontaneously without any intervention. Controversy over treatment and pathogenicity of intestinal spirochaetosis is discussed with review of previous publications.